AUDIT AS AN INDISPENSABLE ELEMENT OF BUSINESS TRADING SECURITY - Jadwiga SZCZOTKA (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej, 2014)
The primary source of economic information in the modern world are the financial statements of entities. Financial statements prepared on the last day of the financial year reflect events occurring in the enterprise business. The purpose of this report is to provide reliable and accurate information about the situation of financial position and results of operations. On the basis of the financial statements contained in the information, a wide range of stakeholders take economic decisions. Examination of financial statements by independent auditors increases the confidence of their addressees to the information contained therein. The topic of this article is to question the use of auditing as a implement in the process of ensuring the security of trade